1/10 x + 70% x = 5/2
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a)13-2(x+1)=7
2.(x+1)=13-7
2.(x+1)=6
x+1=6/2
x+1=3
x=3-1
x=2
a, 13 - 2 ( x + 1 ) = 7
2 .( x + 1 ) = 13 - 7
2 .( x + 1 ) = 6
x + 1 = 6 : 2
x + 1 = 3
x = 3 - 1
x = 4
\(1\)) \(70:\frac{4x+720}{x}=\frac{1}{2}\)
\(\Leftrightarrow\frac{4x+720}{x}=70:\frac{1}{2}\)
\(\Leftrightarrow\frac{4x+720}{x}=140\)
\(\Leftrightarrow\left(4x+720\right):x=140\)
\(\Leftrightarrow4x+720=140.x\)
\(\Leftrightarrow4x-140x=-720\)
\(\Leftrightarrow x.\left(-136\right)=-720\)
\(\Leftrightarrow x=-720:\left(-136\right)\)
\(\Leftrightarrow x=\frac{90}{17}\)
\(2\)) Mình đang nghĩ
\(\frac{70}{3}-\left(x+4\frac{1}{5}\right)=16\)
\(\Rightarrow x+4\frac{1}{5}=\frac{22}{3}\)
\(\Rightarrow x+\frac{21}{5}=\frac{22}{3}\)
\(\Rightarrow x=\frac{22}{3}-\frac{21}{5}\)
\(\Rightarrow x=\frac{47}{15}\)
a) 210 -5.x= 200
<=> 5.x = 210 - 200
<=> 5.x = 10
<=> x = 10 : 5
<=> x = 2
Vậy x = 2
b) 210 - 5 . ( x-10 ) = 200
<=> 5. (x-10) = 210 - 200
<=> 5.(x-10) = 10
<=> x -10 = 10 : 5
<=> x - 10 = 2
<=>x = 12
Vậy x = 12
d)350 : x + 10 = 20
<=> 350 : x = 20 - 10
<=> 350 : x = 10
<=> x = 350 : 10
<=> x = 35
Vậy x = 35
e)36 : ( x - 5 ) = 22
<=> 36 : ( x-5) = 4
<=> x - 5 = 36 : 4
<=> x - 5 = 9
<=> x = 9 + 5
<=> x = 14
Vậy x =14
e) [3 . (70-x) + 5 ] : 2 = 46
<=> [3 . (70-x) + 5 ] = 46 . 2
<=> [3 . (70-x) + 5 ] = 92
<=> 210 - 3.x + 5 = 92
<=>210- 3.x = 92 - 5
<=> 210 - 3.x = 87
<=> 3.x = 210 - 87
<=> 3.x = 123
<=> x = 123 : 3
<=> x = 41
Vậy x = 41
A=1+2+3+...+70
A=(70+1).[(70-1):1+1]:2
A=71.70:2
A=4970:2
A=2485
B=5+10+15+...+100
B=(100+5).[(100-5):5+1]:2
B=105.20:2
B=2100:2
B=1050
a ) \(\frac{3}{7}-\left(\frac{2}{5}+x+\frac{3}{2}\right)=\frac{5}{14}-\left|\frac{4}{35}-\frac{\left(-11\right)}{70}\right|\)
=> \(\frac{3}{7}-\left(\frac{2}{5}+x+\frac{3}{2}\right)=\frac{5}{14}-\left|\frac{4}{35}+\frac{11}{70}\right|\)
=> \(\frac{3}{7}-\left(\frac{2}{5}+x+\frac{3}{2}\right)=\frac{5}{14}-\left|\frac{19}{70}\right|\)
=> \(\frac{3}{7}-\left(\frac{2}{5}+x+\frac{3}{2}\right)=\frac{5}{14}-\frac{19}{70}=\frac{3}{35}\)
=> \(\frac{2}{5}+x+\frac{3}{2}=\frac{3}{7}-\frac{3}{35}=\frac{12}{35}\)
=> \(\frac{2}{5}+x=\frac{12}{35}-\frac{3}{2}=-\frac{81}{70}\)
=> \(x=-\frac{81}{70}-\frac{2}{5}=-\frac{109}{70}\)
b) \(\frac{3}{4}\left(x-8\right)=\frac{5}{7}\left(4-\frac{1}{2}\right)\)
=> \(\frac{3}{4}x-6=\frac{5}{2}\)
=> \(\frac{3}{4}x=\frac{17}{2}\)
=> \(x=\frac{17}{2}:\frac{3}{4}=\frac{34}{3}\)
Câu c,d tự làm nhé
a. \(\frac{3}{7}-\left(\frac{2}{5}+x+\frac{3}{2}\right)=\frac{5}{14}-\left|\frac{4}{35}-\frac{-11}{70}\right|\)
\(\Rightarrow\frac{3}{7}-\left(\frac{19}{10}+x\right)=\frac{5}{14}-\left|\frac{4}{35}+\frac{11}{70}\right|\)
\(\Rightarrow\frac{3}{7}-\frac{19}{10}-x=\frac{5}{14}-\left|\frac{19}{70}\right|=\frac{5}{14}-\frac{19}{70}\)
\(\Rightarrow-\frac{103}{70}-x=\frac{3}{35}\)
\(\Rightarrow x=-\frac{103}{70}-\frac{3}{35}\)
\(\Rightarrow x=-\frac{109}{70}\)
b. \(\frac{3}{4}\left(x-8\right)=\frac{5}{7}\left(4-\frac{1}{2}\right)\)
\(\Rightarrow\frac{3}{4}\left(x-8\right)=\frac{5}{7}.\frac{7}{2}=\frac{5}{2}\)
\(\Rightarrow x-8=\frac{10}{3}\)
\(\Rightarrow x=\frac{34}{3}\)
c. \(\frac{3}{2}-4\left(\frac{1}{4}-x\right)=\frac{2}{3}-7x\)
\(\Rightarrow\frac{3}{2}-1+4x=\frac{2}{3}-7x\)
\(\Rightarrow\frac{1}{2}=\frac{2}{3}-7x-4x=\frac{2}{3}-11x\)
\(\Rightarrow11x=\frac{2}{3}-\frac{1}{2}=\frac{1}{6}\)
\(\Rightarrow x=\frac{1}{66}\)
d. \(4\left(\frac{1}{2}-x\right)-5\left(x-\frac{3}{10}\right)=\frac{7}{4}\)
\(\Rightarrow2-4x-5x+\frac{3}{2}=\frac{7}{4}\)
\(\Rightarrow2-9x=\frac{1}{4}\)
\(\Rightarrow9x=\frac{7}{4}\)
\(\Rightarrow x=\frac{7}{36}\)
a) \(\Rightarrow5\left(x-10\right)=10\)
\(\Rightarrow x-10=2\Rightarrow x=12\)
b) \(\Rightarrow3\left(70-x\right)+5=92\)
\(\Rightarrow3\left(70-x\right)=87\)
\(\Rightarrow70-x=29\Rightarrow x=41\)
c) \(\Rightarrow230+\left[16+\left(x-5\right)\right]=315\)
\(\Rightarrow11+x=85\Rightarrow x=74\)
d) \(\Rightarrow707:\left(2^x-5+74\right)=7\)
\(\Rightarrow2^x-5+74=101\Rightarrow2^x-5=27\)
\(\Rightarrow2^x=32\Rightarrow x=5\)
\(10+2\cdot x=4^5:4^3\)
\(\Rightarrow10+2\cdot x=4^{5-3}\)
\(\Rightarrow10+2\cdot x=4^2\)
\(\Rightarrow10+2\cdot x=16\)
\(\Rightarrow2\cdot x=16-10\)
\(\Rightarrow2\cdot x=6\)
\(\Rightarrow x=\dfrac{6}{2}=3\)
__________________
\(2\cdot x-6^2:18=3\cdot2^2\)
\(\Rightarrow2\cdot x-36:18=12\)
\(\Rightarrow2\cdot x-2=12\)
\(\Rightarrow2\cdot x=12+2\)
\(\Rightarrow2\cdot x=14\)
\(\Rightarrow x=\dfrac{14}{2}=7\)
_________________
\(70-5\cdot\left(x-3\right)=3\cdot2\)
\(\Rightarrow70-5\cdot\left(x-3\right)=6\)
\(\Rightarrow70-5x+15=6\)
\(\Rightarrow-5x+15=6-70\)
\(\Rightarrow-5x+15=64\)
\(\Rightarrow-5x=64-15\)
\(\Rightarrow-5x=49\)
\(\Rightarrow x=-\dfrac{49}{5}\)
1/10 x + 70% x = 5/2
=>1/10 x + 70/100 x = 5/2
=>1/10 x + 7/10 x = 5/2
=>x.(1/10+7/10)=5/2
=>x.8/10=5/2
=>x.4/5=5/2
=>x=5/2:4/5
=>x=5/2.5/4
=>x=25/8
1/10x + 70% x = 5/2
=> 1/10x + 70/100 x = 5/2.
=> 1/10x + 7/10x = 5/2
=> x.( 1/10 + 7/10 ) = 5/2
=> x . 8/10 = 5/2
=> x . 4/5 = 5/2
=> x = 5/2 : 4/5
=> x = 5/2 x 5/4
=> x =25/8